Managing a Scholarly Journal in Nigeria: Issues, Concerns and Challenges - EDEWOR, NELSON; EJITAGHA, STELLA (MiddleBelt Journal of Library and Information Science, 2020)
The purpose of this paper is to provide an overview of the continuous changes and challenges of scholarly publishing and knowledge dissemination in an era of Internet revolution. It draws lessons from a Nigerian Journal – Information Impact: Journal of Information and Knowledge Management. The paper analyses the impact of the online edition of the journal as it creates opportunities for global visibility and impact. It outlines the challenges (content, managerial, quality and review issues) for publishers in developing the full potentials of open access. The paper highlights the benefits of publishing electronic copies for authors and their institutions. It addresses the roles and responsibilities of libraries within academic institutions in charting clear institutional policies for access to journals. The paper concludes that with regards to the future of scholarly journals, particularly in relation to peer review mechanism and quality control, editorial boards have a very important role to perform. Difficulties in scholarly journal publishing in Nigeria must be addressed to ensure maximum benefits of the open access movement in bridging the knowledge gap. The study recommends among others that editors and publishers of scholarly journals have to be aware of the revolution taking place in scholarly communication and influence it as much as possible, for the benefit of the Nigerian scientific and scholarly communities. They must become skilled in the use of new applications and be ready to take advantage of the new opportunities created by the ready availability of open access resources